Dinamika Keputusan Investasi UMKM di Tengah Ketidakpastian Ekonomi: Studi Kualitatif pada Sektor Kuliner - Nurul Ahillatun Nadifah (https://journal.metanusantara.com/jenius/index.php/jem, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, especially in the culinary sector, which is experiencing rapid growth. However, the dynamics of economic uncertainty due to the global crisis, inflation, and changes in macroeconomic policies pose great challenges in making investment decisions for MSME players. This study aims to analyse the factors that influence investment decisions of MSMEs in the culinary sector in the face of economic uncertainty. This research uses a qualitative approach with a case study method on several culinary MSMEs in Indonesia. Data were collected through in-depth interviews with business owners and direct observation, then analysed using thematic analysis techniques. The results show that MSMEs' investment decisions are influenced by internal factors, such as capital, business strategy, and managerial skills, as well as external factors, such as government policies, market conditions, and access to digital technology. In situations of economic uncertainty, MSMEs tend to implement more flexible investment strategies, such as product diversification, cost efficiency, and marketing digitalisation. This research enriches the literature on MSME investment by highlighting the importance of business strategy adaptation in the face of economic uncertainty. The results also provide recommendations for the government and stakeholders to design policies that support the sustainability of MSMEs in the culinary sector.